A sensitive UPLC/ESI/MS/MS method for concomitant quantification of active plant constituent combinations in rat plasma after single oral administration. Issue 8 (14th February 2022) - Chaudhari, Vishal Sharad; Jala, Aishwarya; Murty, Upadhyayula Suryanarayana; Borkar, Roshan M.; Banerjee, Subham
Abstract : UPLC/ESI/MS/MS mediated bio-analytical method to quantify quercetin and piperine in rat plasma simultaneously. Application to exploration of bioavailability enhancement through nano carriers. Abstract : Ultra-performance liquid chromatography electrospray ionization tandem mass spectrometry (UPLC/ESI/MS/MS) for the concomitant quantification of active plant constituents, namely quercetin and piperine, in rat plasma was developed and validated to assess pharmacokinetics after a single oral administration. Liquid–liquid extraction technique with ethyl acetate and n -hexane (1 : 1) was used, and fisetin was added as an internal standard (IS). Effective chromatographic separation of quercetin, piperine and IS was executed on a Waters Acquity BEH C18 column (50.0 mm × 2.1 mm, 1.7 μm) using formic acid both (0.1% w/v) in water (A) and acetonitrile (B) as the mobile phase in gradient mode. For detection purposes, positive electrospray ionization (ESI) mode was used with multiple reaction monitoring (MRM) mode for estimation using [M + H] + fragment ions m / z 303.04 → 152.9 for quercetin, 286.12 → 201.04 for piperine and 287.01 → 136.93 for IS. The method was linear over the calibration range of 0.1–200 ng mL −1 . The lower limit of quantification (LLOQ) of quercetin and piperine was obtained as 0.1 ng mL −1 in rat plasma, along with negligible matrix effect and acceptable stability. Furthermore, the bioanalytical method was successfully implemented to determine the pharmacokinetic profiles of quercetin-and piperine-enriched nanostructured lipid carriers (NLCs) in rat plasma after oral administration. The enhancement in the oral bioavailability of quercetin and piperine was 20.72 and 4.67 fold, respectively, compared to their native pristine dispersions. Future exploration of the concentrations of these active constituents in human plasma and organs is feasible using this sensitive, validated UPLC/ESI/MS/MS method.